Autorzy:Dubiecka-Kruk Barbara, Dubiecka Anna, Bazyluk Anna
Wydawnictwo:WSiP
Rok wydania:2014
Podane wyrażenie zapisz w najprostszej postaci 4.5 gwiazdek na podstawie 8 opinii

`a)\ (x+1)^2-x^2+2=ul(x^2)+2x+ul(ul1)-ul(x^2)+ul(ul2)=2x+3` 

`b)\ (a-2)^2+4-a^2=ul(a^2)-4a+ul(ul4)+ul(ul4)-ul(a^2)=-4a+8` 

`c)\ (x+4)^2+(x-4)^2=ul(x^2)+ul(ul(8x))+ul(ul(ul(16)))+ul(x^2)-ul(ul(8x))+ul(ul(ul(16)))=2x^2+32` 

`d)\ (2a-1)^2-(2a+1)^2=4a^2-4a+1-(4a^2+4a+1)=` 

`\ \ \ =ul(4a^2)-ul(ul(4a))+ul(ul(ul(1)))-ul(4a^2)-ul(ul(4a))-ul(ul(ul(1)))=-8a`